What Drives Rapid Internationalization – A Case of Malaysian SMEs - Saqib, Sahabat (2008)
Traditionally, internationalization has been assumed to be activity that requires significant amounts of time and resources. Owing to this, firms took time to establish themselves in their domestic markets before they started to expand into overseas markets. However, over the past decade or so numerous small and medium firms have sprung up, these companies have a global orientation right from their inception. These firms have been termed Born Globals. In light of the aforementioned, this dissertation examines factors influencing the rapidinternationalization of small and medium enterprises in Malaysia in order to comprehend why small and medium enterprises are increasingly international in nature at or soon after their inception. A majority of prior research conducted in the subject of study has been carried out on high-tech companies. Therefore this research included firms from an array of industries in efforts of capturing a more holistic picture of factors that influence the internationalization decision of the firms in relation to speed of internationalization. The study qualitatively identifies leading influential factors amongst five firms, via conducting interviews with key decision makers at the companies in question. Among the drivers of rapid internationalization, firstly the role of the entrepreneur, especially their international experience, executive networks, and a global vision were found significant. Secondly, the study also found the role of network relations with distributors, strategic alliance partners, customers and industrial and trade associations to be essential to rapid internationalization. Lastly, the influence of external environmental factors such as domestic and foreign market conditions and technological advancements was also found to be particularly significant.